Armenia : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
This detailed assessment report focuses on antimoney laundering and combating the financing of terrorism (AML/CFT) for Armenia. The report reveals that Armenia's financial system remains small and bank dominated. Total assets of the banking sector accounted for approximately 91 percent of the assets in the financial system. Most banks are domestically owned but there is a major foreign presence in the system. The nonbank financial sector plays a small role in financial intermediation.